Wind tunnel experiments on a NACA 633‐418 airfoil with different types of leading edge roughness. Issue 11 (3rd May 2021) - Krog Kruse, Emil; Bak, Christian; Olsen, Anders Smærup
Abstract: The NACA 633 ‐418 airfoil has been tested in the new Poul la Cour Wind Tunnel at the Technical University of Denmark, Risø campus, to expand the publicly available data of airfoils with leading edge roughness. The airfoil was constructed with an exchangeable leading edge. The clean airfoil showed good agreement with results from other high‐quality wind tunnels. The airfoil was equipped with three heights of zigzag tape, a trip strip, three sandpaper types, and leading edge cavities with different modifications. In general, increasing zigzag tape heights reduce the maximum lift, whereas the increase in drag is less affected by the zigzag tape height. Almost the same reduction in maximum lift is seen for the different sandpaper types. However, the drag increases with the coarseness of the sandpaper. The highest zigzag tape and coarsest sandpaper resulted in the highest penalty on the aerodynamics. A combination of sandpaper and cavities showed the largest reduction in maximum lift and the highest increase in drag.